Evaluation of Total Mixed Rations in Terms of Nutrient Utilisation, Methane Production and Gaseous Exchange in Cattle and Buffaloes - Sinha, S. K.; Chaturvedi, V. B.; , P. Singh; Verma, A. K.; , Swati Shivani (Indian Journal of Animal Nutrition, 2018)
The present experiment was conducted to find out the effect of different ratios of concentrate, wheat straw and green fodder in rations on methane (CH4) production, gaseous exchange and heat production in crossbred cattle and buffaloes. After every one month of experimental feeding, CH4, heat production and gaseous exchange (CO2 and O2) were determined using open circuit respiration calorimetry in six adult crossbred cattle (Bos taurus × Bos indicus) and buffaloes (Bubalus bubalis) with average BW of 257.011±7.34 and 319.56±10.86 kg, respectively (age: 12-18 mo.). Experimental feeding consisted of three ratios of concentrate, wheat straw and green maize fodder i.e. 60: 20: 20 (T1), 40:30:30 (T2) and 20:40:40 (T3) fed as TMR alternatively to each group. The DM and OM intake in all the treatments and species were similar. The digestibility of DM and OM was different (P<0.01) among treatments but similar in both the species. Total CH4 production (L/d) was lower (P<0.01) in crossbred cattle than that in buffaloes and it was higher (P<0.01) on high roughage diet. Emission of CH4 expressed as L/kg W0.75 as well as L/kg DMI, OMI, DMD and OMD was higher (P<0.01) in buffaloes than cattle. O2 consumption (L/kg W0.75) was higher (P<0.01) in crossbred cattle than that in buffaloes; however, CO2 production (L/kg W0.75) was similar across species and treatments. The heat production was lower (P<0.01) in buffaloes than cattle. The mean respiratory quotient ranged from 0.91 to 0.95 in crossbred cattle and buffaloes. It was concluded that DM and OM intake in buffaloes and cattle was similar. However, the values of urinary N excretion and respiratory quotient in buffaloes were higher than that in cattle. Heat production and O2 consumption in buffaloes were lower than that in cattle. Furthermore, at similar level of DMI, buffaloes had higher CH4 emissions than cattle and higher proportion of concentrates in the diet decreased CH4 emissions linearly in both the species.